Personal Hygiene And Skin Complaints Among Students At As’ad Islamic Boarding School - rizkiyani noor, amadea; Kusdiyah, Erny; Nofri Enis, Rina (Scientific Of Environmental Health and Diseases, 2025)
Background: Skin disorders are an important component of childhood morbidity. Islamic boarding schools are among the environments with a high risk of developing skin problems such as itching, redness, white spots, or bumps. One preventive measure to reduce the risk of skin diseases is maintaining good personal hygiene. This study aimed to describe personal hygiene and skin complaints among students. Method: This descriptive observational study with a cross-sectional design was conducted at As’ad Islamic Boarding School, Jambi City, in November 2024. The sample consisted of 97 students who reported skin complaints. Results: Of the 97 participants, 61 students (62.9%) had good personal hygiene, while 36 students (37.1%) had poor personal hygiene. A total of 84 students (86.6%) reported itching, 53 students (54.6%) reported bumps, 36 students (37.1%) had red rashes, 20 students (20.6%) reported white/reddish spots, and the least frequently reported complaint was a hot or burning sensation (7 students; 7.2%). In addition, 38 students (39.2%) experienced recurrent complaints. Conclusion: Most students tended to have good personal hygiene, including maintaining cleanliness of the skin, hands, and nails, as well as clothing, towels, beds, and bed sheets. However, itching was the most common skin complaint among students at As’ad Islamic Boarding School.